Anti-Inflammatory Properties of Mimosa pudica: Isolation, Characterization, and Biological Evaluation of Bioactive Compounds. - Yadav, Sushil; S, Rajasekaran (Journal of Neonatal Surgery, 2025)
Mimosa pudica L. (Sensitive Plant) has a longer history as a medicinal plant and is used for the treatment of inflammation and pain. Due to the plant's thigmonastic response and the various cultures which use the plant, the current study expands on the plant's medicinal uses to the treatment of inflammation, focusing on the isolation, characterization and the medicinal biological uses of its active compounds. Its habitat includes lowland tropical rainforests, savannas, tropical and subtropical dry forests, thorn scrub, mid-elevation subtropical forests, deserts, grasslands, and wetlands. The approach for this intends designed study was extraction as the basis of a systematized and comprehensive study using various chromatographic techniques for the isolation and characterization steps of the study. Ethyl, methyl, aqua, and chloroform extractions were done to capture more of the active constituents. The ethyl acetate extract's anti-inflammatory properties were the most notable within the received extracts. The bioactive constituent was isolated and characterized as quercetin, using a combination of techniques including UV, FT-IR, NMR, and Mass Spectroscopy. Biological testing on quercetin showed the expected anti-inflammatory activity comparable to diclofenac on both acute and chronic inflammation (carrageenan-induced paw edema and cotton pellet-induced granuloma tests). Moreover, the compound decreased CRP, TNF-α, and IL-6. This is further evidence of the clinical argument for the pseudoinflammatory uses of Mimosa pudica. This also means the uses of Mimosa pudica L. for quercetin-containing therapeutic agents is justified as quercetin is the most active compound within the study. These results demonstrate the considerable ability of Mimosa pudica to treat diseases connected to inflammation and serves as the basis for upcoming clinical research and drug design